Weed management in mechanized-sown, zero-till dry-seeded rice - Chauhan, Bhagirath S.; Abugho, Seth B. (Cambridge University Press, 2013)
Weeds are the main constraint in the adoption of zero-till, dry-seeded rice systems because weeds and rice emerge simultaneously in these systems, and there is no standing water at crop establishment to suppress weeds. A study was conducted during the wet season of 2011 and the dry season of 2012 at the International Rice Research Institute to evaluate the performance of different herbicides in mechanized-sown, zero-till dry-seeded rice. Among the treatments evaluated, oxadiazon followed by penoxsulam + cyhalofop followed by one hand-weeding at 42 d after sowing, provided 23 to 35% higher yield than the nontreated control. The yields in the oxadiazon-treated plots were similar to those in the weed-free plots. Some weed species, including eclipta and doveweed, were not controlled by the evaluated herbicides. Therefore, there is a need to evaluate additional herbicides and to integrate them with cultural weed management strategies to manage such problematic weeds.